Environmental impact assessment handbook : a practical guide for planners, developers and communities. - Carroll, Barbara, 1950-; Fothergill, Josh; Murphy, Jo; Turpin, Trevor (ICE Publishing, 2020)
Environmental Impact Assessment Handbook, Third edition offers a comprehensive practical guide to the requirements of environmental impact assessment (EIA) in accordance with UK regulations. Explaining the EIA process and legal procedures in a clear and straightforward way, the authors employ their extensive practical experience to cover each of the steps and associated studies needed to undertake an EIA and to produce a successful environmental statement.
Previous edition published 2009.
Keywords: Environmental impact analysis -- Great Britain -- Handbooks, manuals, etc.; Environmental impact statements -- Great Britain -- Handbooks, manuals, etc.; elektronické knihy; electronic books